Loss of TAZ after YAP deletion severely impairs foregut development and worsens cholestatic hepatocellular injury - Gabdulkhakova, Adelya; Krutsenko, Yekaterina; Zhu, Junjie; Liu, Silvia; Poddar, Minakshi; Singh, Sucha; Ma, Xiaochao; Nejak-Bowen, Kari; Monga, Satdarshan P.S.; Molina-Molina, Laura (Hepatology communications, 2023)
We previously showed that loss of yes-associated protein 1 (YAP) in early liver development (YAPKO) leads to an Alagille syndrome-like phenotype, with failure of intrahepatic bile duct development, severe cholestasis, and chronic hepatocyte adaptations to reduce liver injury. TAZ, a paralog of YAP, was significantly upregulated in YAPKO hepatocytes and interacted with TEA domain family member (TEAD) transcription factors, suggesting possible compensatory activity.,
Gesehen am 05.10.2023